Assessment of Turbulence Model for Cross-Flow Pico Hydro Turbine Numerical Simulation - Siswantara, Ahmad Indra; Budiarso, Budiarso; Prakoso, Aji Putro; R Gunadi, Gun Gun; Warjito, Warjito; Adanta, Dendy (CFD Letters, 2021)
This study will be assessing some turbulence model for numerical simulation in Pico hydro cross-flow turbine with three variables like errors, time per iteration and average iterations to converged. The computational fluid dynamics (CFD) methods in this study using ANSYS™ FLUENT® 18.2 academic licensed with two-dimensional (2D) and feature six-degrees of freedom (6-DoF). Then, validation and verification were done by comparing with previous study. There are six turbulence model that compared: standard wall function k-?, scalable wall function k-?, standard wall function RNG, scalable wall function RNG, standard transitional SST, and transitional SST with curvature corrections. From the results, all the turbulent models give the almost similar results. However, if by error assessment, the RNG turbulence model with scalable wall function was the most accurate than others. By number of timestep iterations assessment, the transitional SST with curvature correction resulting more quickly to convergence than others. By timestep calculations times, the standard transitional SST has relative average calculation timestep smaller than others. Thus, based on assessment the turbulence model suitable for numerical simulation in pico hydro cross-flow turbine is standard transitional SST.